Arterial tissue transcriptional profiles associate with tissue remodeling and cardiovascular phenotype in children with end-stage kidney disease - Freise, Christian; Schäfer, Betti; Bartosova, Maria; Bayazit, Aysun; Bauer, Ulrike; Pickardt, Thomas; Berger, Felix; Rasmussen, Lars Melholt; Jensen, Pia Søndergaard; Laube, Guido; Mencarelli, Francesca; Arbeiter, Klaus; et al. (Scientific reports, 2019)
Chronic kidney disease (CKD) greatly increases the risk for cardiovascular disease (CVD). However, molecular mechanisms underlying CKD-induced arterial remodeling are largely unknown. We performed a systematic analysis of arterial biopsies from children with stage 5 predialysis CKD participating in the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4 C) study. For comparison, we studied biopsies from children without CKD, coronary bypass vessels from adults with atherosclerotic coronary heart disease without CKD and aortic sections of subtotally nephrectomized rats. In pediatric CKD patients, gene expression was correlated to the cardiovascular phenotype assessed by surrogate end-points. The arterial calcium content correlated with the intima-media thickness (IMT) of biopsied vessels from pediatric CKD patients, was markedly increased compared to biopsies from children without CKD and comparable to adult coronary bypass patients. Significant transcriptional changes included ECM components, pro-calcifying factors, and physiological calcification inhibitors; most were highly accordant with changes observed in adults with atherosclerosis and in uremic rats. Individual gene expression levels were significantly associated with the left ventricular mass index and carotid intima media thickness. Thus, inflammatory processes (TNF, IL-10), calcification inhibitors (CA2), the Wnt-pathway (FGF-2) and foremost, ECM components (HMGA1, VNN1, VCAN), impact pathobiological responses in arteries from children with CKD.